Pergeseran Dominasi Gulma Kebun Kelapa Sawit IPB Jonggol, dan Kemungkinan Resistensi terhadap Herbisida Glifosat - Bilkis, Faras Gaitsa; Muhamad Achmad Chozin; Dwi Guntoro, (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2022)
Vegetation analysis has been done periodically at IPB oil palm plantations in Jonggol to identify the dominant weeds on the 1-year-old-mature plant (2016), 3-year-old-mature plant (2018), and 5-year-old-mature plant (2020). The study consisted of two experiments. The first experiment was to determine the dominant weed shift, while the second was to assess the possibility of weed resistance to glyphosate herbicide. Experiment I conducted vegetation analysis with the quadrant method 1 m x 1 m on 5 blocks; 20 samples were taken randomly from each block so that there were 100 observation samples. Experiment II planted seeds of weeds selected from experiment I, and as control, seeds of weeds from locations that never received herbicide. The amino acids observed are associated with glyphosate’s modes of action, namely phenylalanine, tyrosine, and L-tryptophan. Vegetation analysis showed there had been a shift in dominant weeds. In 2016, the dominant weed was Rolandra fruticosa and Melastoma malabathricum, in 2018 the Ottochloa nodosa, and in 2020 O. nodosa and Cyrtococcum patens. Asystasioa gangetica continues to increase in population. Resistance ratios, test weeds O. nodosa and C. patens are categorized as low resistance. The content of phenylalanine, tyrosine, and L-tryptophan test weed O. nodosa is higher than that of susceptible weed O. nodosa.Keywords: amino acids, dominant weeds, resistance ratio, vegetation analysis